Pseudotumor Cerebri Presenting Unilateral Papilledema Associated with Iron-deficiency Anemia - Costa, Fernando Antônio de Oliveira; Fabião Neto, Othello Moreira; Gago, Guilherme; Martins, Otávio Garcia; Gibbon, Frederico de Lima; Nogueira, Leonardo Mendes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Pseudotumor cerebri is a relatively common pathology that is characterized by intracranial hypertension in the absence of mass lesions. It commonly affects young and obese women, and its presentation with visual loss and bilateral papilledema is well-described in the literature. We present a case of a 44-year-old, non-obese, female patient presenting with unilateral papilledema and iron-deficiency anemia. This case emphasizes this unusual presentation and the rare association with iron deficiency.
Keywords: pseudotumor cerebri; idiopathic intracranial hypertension; unilateral papilledema; iron-deficiency anemia